Frequency Comb Fiber Generator Based on Photonic Bandgap Amplifier - Aleksei Abramov; Dmitry Korobko; Igor Zolotovskii (Photonics, 2023)
We report on a model of a fiber frequency comb generator that develops an approach to harmonically mode-locked fiber laser design based on dissipative four-wave mixing. In our version of this approach, we assume an amplifying one-dimensional photonic crystal as a key cavity element combining the properties of an intra-cavity filter and a power amplifier. Using standard equations describing the signal transformation in the ring cavity and the output fiber cascade, we have demonstrated the possibility of the application of the proposed model as a generator of broadband frequency comb with controllable line spacing.